Implementing multi-tiered systems of support in rural schools: a practice perspective for improving mental health care for underserved youths - Kearney, Christopher A.; Fensken, Michael; Dupont, Randolph (Frontiers in Education, 2025)
Rates of mental disorder for youth have increased substantially over recent years and this trend, coupled with persistent barriers to community-based care, has led researchers and others toward a “where they are” approach that emphasizes preventative and health promotion practices within ecologically valid environments such as schools. A key mechanism of this approach involves multi-tiered systems of support (MTSS) models that allocate supports based on student need across multiple domains of functioning. MTSS models have been implemented with moderate success but students in rural districts may be underserved. This article introduces a blueprint for a sample MTSS approach in rural schools by initially presenting their challenges and advantages as well as implementation science frameworks, and particularly the School Implementation Strategies, Translating ERIC Resources (SISTER) project, geared toward educational settings. The blueprint incorporates SISTER pillars rated highest for importance and feasibility throughout linchpin strategies to set the basis for the MTSS model; readiness strategies to determine needs, structure, and feasibility; Tier 1 strategies to implement preventative practices and address emerging cases; Tier 2 strategies to provide early intervention services for acute cases; Tier 3 strategies to provide intensive intervention services for chronic and severe cases; and strategies to enhance sustainability (including fidelity) and expansion. The blueprint thus represents a blending of emerging implementation science ideas with real-world constraints often evident in rural schools to provide a practice perspective and one set of ideas to promote discussion and innovation for a key underserved student constituency.